Organizational Culture And Islamic Work Ethics On Teacher Performance: The Important Role Of Spiritual Work Motivation In Mediating - Purnama, Chamdan; Rahmah, Mirhamida; Fatmah, Dinda; Hasani, Syaiful; Rahmah, Yusriyah; Rahmah, Zakiyah Zulfa (Jurnal Ilmiah Ekonomi Islam, 2024)
The purpose of this study was to examine the influence of organizational culture and Islamic work ethic on teacher performance through spiritual work motivation. The sample of this study was 196 respondents of Islamic boarding school teachers in Madura region. The test method uses purposive random sampling with a minimum of occupying the homeroom level. Using the Smart PLS version 3.0 analysis technique results that organizational culture and Islamic work ethic does not directly affect teacher performance but indirectly affect teacher performance through Spiritual Work Motivation The results are relied upon to add knowledge to enrich the theory of human resource management and Islamic boarding school behavior theory, especially regarding teacher performance. In addition, it is hoped that this new model will assist future research in paying attention to the factors that can affect teacher performance. This research is a novelty research which develops the concept of work motivation into Spiritual Work Motivation based on Quran and Sunnah along with the principles of Islamic boarding schools in accordance with the research context, namely in Islamic boarding schools.